2020
DOI: 10.1111/pace.14090
|View full text |Cite
|
Sign up to set email alerts
|

Management of systemic fungal infections in the presence of a cardiac implantable electronic device: A systematic review

Abstract: Evidence to inform the management of systemic fungal infections in the setting of a cardiac implantable electronic devices (CIED), such as a permanent pacemaker or implantable cardioverter‐defibrillator, is scant and limited to case reports and series. The available literature suggests high morbidity and mortality. To better characterize the shared experience of these cases and their outcomes, we performed a systematic review. We investigated all published reports of systemic fungal infections—fungemia and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Complete device extraction should be considered even in the absence of vegetations in the setting of persistent or relapsing Gram-positive bacteraemia or fungaemia after a course of appropriate antibiotic therapy, if there is no other identified source (see Figure 13). 681 In all instances of lead extraction, procedural risk should be carefully evaluated taking into account lead dwell time, pacemaker dependency, patient frailty, and other co-morbidities within the process of shared decision-making. 703 Lead extraction should be performed, without delay (i.e.…”
Section: Device Extractionmentioning
confidence: 99%
“…Complete device extraction should be considered even in the absence of vegetations in the setting of persistent or relapsing Gram-positive bacteraemia or fungaemia after a course of appropriate antibiotic therapy, if there is no other identified source (see Figure 13). 681 In all instances of lead extraction, procedural risk should be carefully evaluated taking into account lead dwell time, pacemaker dependency, patient frailty, and other co-morbidities within the process of shared decision-making. 703 Lead extraction should be performed, without delay (i.e.…”
Section: Device Extractionmentioning
confidence: 99%
“…A recent study by Meena et al (2022), which retrospectively reviewed the literature for 250 cases of fungal endocarditis, highlighted improved survival outcomes in patients with surgical intervention (Hazard ratio 0.20, 95% confidence interval 0.09–0.42; p-value < 0.001) [ 3 ]. Improvement in patient survival parameters and clearance of blood cultures after extraction of cardiac implant electronic devices was reported in a retrospective study by Baman et al [ 9 ]. While the statistics reiterate the brighter outcomes with valve replacements and device extractions, real-life clinical cases get complicated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that in cases of fungaemia in the presence of implantable cardiac devices, extraction of the devices was associated with both increased survival to discharge and increased clinical recovery or cure. 12 In the case of native valve endocarditis, the IDSA recommends the use of lipid formulation amphotericin B with the addition of flucytosine in certain cases, or treatment with high dose echinocandins, such as caspofungin. Amphotericin B is a polyene antifungal with a broad spectrum of activity that has been associated with nephrotoxicity 13 and other side effects in up to 50% of cases.…”
Section: Discussionmentioning
confidence: 99%